2017
DOI: 10.1093/aje/kww214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Diastolic Dysfunction According to Different Classification Criteria

Abstract: Heart failure with preserved ejection fraction is often preceded by diastolic dysfunction (DD). Of several published DD criteria, it is unclear which, if any, are applicable to data obtained in epidemiologic cohorts. We evaluated the prevalence of DD using previously published definitions in a population-based study, the Coronary Artery Risk Development in Young Adults (CARDIA) Study, using data gathered in 2010-2011. Echocardiography was performed on 3,474 individuals (mean age = 50.2 years) at the CARDIA yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…49 Epidemiologic studies have also highlighted the significant differences in prevalence of diastolic dysfunction various population cohorts between prior and current guidelines (Table 2), with variation in the prevalence of diastolic dysfunction up to 30% between different guidelines and a significant proportion still being labeled as ''indeterminant'' based on guidelines. 50,51 The ability of the guidelines to accurately distinguish normal vs abnormal left sided filling pressures has shown mixed results. While some studies have suggested high degree of correlation between non-invasive and invasive measures of left sided filling pressures in patients, 13,[52][53][54] other studies have suggested a modest correlation at best.…”
Section: Non-invasive Evaluation Of Diastolic Function By Echocardiogmentioning
confidence: 99%
“…49 Epidemiologic studies have also highlighted the significant differences in prevalence of diastolic dysfunction various population cohorts between prior and current guidelines (Table 2), with variation in the prevalence of diastolic dysfunction up to 30% between different guidelines and a significant proportion still being labeled as ''indeterminant'' based on guidelines. 50,51 The ability of the guidelines to accurately distinguish normal vs abnormal left sided filling pressures has shown mixed results. While some studies have suggested high degree of correlation between non-invasive and invasive measures of left sided filling pressures in patients, 13,[52][53][54] other studies have suggested a modest correlation at best.…”
Section: Non-invasive Evaluation Of Diastolic Function By Echocardiogmentioning
confidence: 99%
“…We thank Drs. Pandey and Berry for providing insightful commentary (1) on our study (2), which demonstrated poor overlap among currently used definitions of diastolic dysfunction (DD) in a middle-aged cohort. Pandey and Berry caution against a strategy of trying to find "perfect" echocardiographic criteria for DD and urge that investigators consider the incorporation of blood-based markers and exercise capacity into the definition of DD (1), as these markers can help place echocardiographic measurements into proper context from a clinical point of view.…”
mentioning
confidence: 99%
“…Echocardiographic criteria for grading diastolic function evolved over the course of the study period (1997–2014). 22 Thus, our approach of accepting the grade assigned by the interpreting cardiologist reflects their integration of the available data and reflects standards of clinical practice at the time the echocardiograms were interpreted. However, interobserver variability is a potential source of bias in analyses examining individuals with repeated TTE assessments.…”
Section: Discussionmentioning
confidence: 99%